Elemental Composition of Kelp Thalli (Laminariae thalli) of Various Origins - V. M. Shchukin; E. A. Khorolskaya; N. E. Kuz’mina; I. P. Remezova; V. V. Kosenko (Регуляторные исследования и экспертиза лекарственных средств)
Brown seaweeds (Laminariaceae) vary considerably in the content of toxic and essential elements; these variations depend on the taxonomic group and geographical factors. Seaweeds are extensively used in the food industry and widely applied in medicine for both humans and animals. Therefore, it is relevant to examine the correlation between the elemental composition and the geographical origin of kelp thalli obtained from different sources.The aim of the study was to collect, collate, and analyse primary and secondary data on the accumulation of essential, toxic and potentially carcinogenic elements, including iodine, in the thalli of brown seaweeds (Laminariaceae).Materials and methods. This study investigated the concentrations of 17 elements in Laminaria spp. (Al, As, Cd, Cr, Co, Cu, Fe, Hg, Mn, Mo, Ni, Se, Pb, Sr, V, Zn, and I). Experiments were conducted on an Agilent 7900 inductively coupled plasma mass spectrometer. The authors studied publications on the elemental composition of brown seaweeds (Laminariaceae) using literature search and data analysis methods.Results. This article reflects the updated classification of brown seaweeds (Laminariaceae) and summarises information about the mechanisms by which iodine and other elements accumulate in the thallus. The authors established species-specific variations in the order of element uptake and in the accumulation of elemental toxicants. The mutual influence of elements on their accumulation in brown seaweeds (Laminariaceae) was evaluated using Spearman’s rank correlation coefficients.Conclusions. The study results can inform the implementation of a risk-based quality control strategy for herbal medicinal products aimed at reducing human exposure to toxic elements. The authors suggest that the upper limit of iodine content in kelp-based food products should be standardised.